Kemaslahatan Sosial Vaksin sebagai Instrumen Medis Penanggulangan Covid-19 dalam Perspektif Islam - Abd Hannan (Asy-Syari’ah : Jurnal Hukum Islam, 2022)
Abstract One of the instruments to overcome the Covid-19 pandemic is the use of vaccines. Based on medical studies, vaccines contain a number of benefits, especially in building immunity. Only in many cases, not a few people 'reject' the benefits of vaccines on the pretext of religion, especially regarding the legal clarity of permissibility and the content of substances that are considered dangerous (dharurat) for health. This study examines the social benefits of vaccines in dealing with Covid-19 from an Islamic perspective. There are two research questions raised in this study, What is meant by the concept of social benefit in an Islamic perspective? How does vaccination provide social benefits to its users? Methodologically, this study uses qualitative research, the data used comes from two sources, primary and secondary sources. After conducting an in-depth analysis through the use of benefit theory, this study found two important findings; First, vaccines are an instrument of disease prevention that is common in medical circles. Its main function is to carry out prevention through the formation of immune power so that the body will become more immune to virus transmission. In the context of dealing with Covid-19, medically, people who have been vaccinated have a lower risk of transmission than those who have not; Second, from an Islamic perspective, the dimensions of the benefits of using vaccines can be seen from three aspects; 1) The effect is that vaccines have the main function of forming self-immunity. The use of vaccines has a significant influence in suppressing the movement and transmission of Covid, so that the number of spikes and victims can be kept to a minimum; 2) The scope is that vaccines provide two-way protection benefits at the same time, namely self-protection and protection of the environment, family and society in general; 3) The aspect of the strength of the argument, that the use of vaccines has a strong enough Islamic basis or argument, both on the basis of permissibility law and related to its benefit aspects. Keywords: Covid-19 vaccine, Islamic perspective, social benefits of vaccines Abstrak Salah satu instrumen penanggulangan pandemi Covid-19 adalah penggunaan vaksin. Berdasarkan kajian medis, vaksin mengandung sejumlah kemaslahatan, khususnya dalam membentuk kekebalan tubuh. Hanya dalam banyak kasus, tidak sedikit masyarakat ‘menolak’ kemaslahatan vaksin atas dalih agama, khususnya menyangkut kejelasan hukum kebolehan dan kandungan zatnya yang dianggap berbahaya (dharurat)bagi kesehatan. Studi ini mengkaji kemaslahatan sosial vaksin dalam penanggulangan Covid-19 perspektif Islam. Terdapat dua pertanyaan penelitian yang diangkat dalam kajian ini, Apa yang dimaksud dengan konsep kemaslahatan sosial dalam perspektif Islam? Bagaimana vaksinasi memberi kemaslahatan sosial terhadap penggunanya? Secara metodologi, kajian ini mempergunakan jenis penelitian kualitatif, data yang digunakan berasal dari dua sumber, sumber primer dan sekunder. Setelah melakukan analisa mendalam melalui penggunaan teori maslahat, penelitian ini mendapati dua temuan penting; Pertama, vaksin merupakan instrumen pencegahan penyakit yang sudah lazim di kalangan medis. Fungsi utamanya adalah melakukan pencegahan melalui pembentukan daya imun sehingga tubuh akan menjadi lebih kebal terhadap penularan virus. Dalam konteks penanggulangan Covid-19, secara medis orang yang sudah melakukan vaksinasi memiliki risiko penularan lebih rendah daripada yang belum; Kedua,ditinjau dari perspektif Islam, dimensi kemaslahatan penggunan vaksin dapat dilihat dari tiga aspek; 1) Pengaruhnya, bahwa vaksin memiliki fungsi utama membentuk daya imun diri. Penggunaan vaksin memiliki pengaruh signifikan dalam menekan pergerakan dan penularan Covid, sehingga jumlah lonjakan dan korbannya dapat ditekan seminim mungkin; 2) Cakupannya, vaksin memberi manfaat perlindungan dua arah sekaligus, yakni perlindungan diri dan perlindungan terhadap lingkungan, keluarga dan masyarakat secara umum; 3) Aspek kekuatan dalilnya, bahwa penggunaan vaksin memiliki landasan atau dalil keislaman cukup kuat, baik landasan terkait hukum kebolehan maupun terkait aspek kemaslahatannya. Kata Kunci: Vaksin Covid-19, perspektif Islam, kemaslahatan sosial vaksin